Dirty money : on financial delinquency - Ruggiero, Vincenzo (Oxford : Oxford University Press, 2017)
Navigating financial crashes of the Late Middle Ages up to the present day and analysing them through the lenses of classical, positivist, functionalist and Marxist criminology, this work explores the growth of grey areas in the financial world and our understanding, or misunderstanding, of financial delinquency.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 6, 2017).
Keywords: Financial crises -- History; Commercial crimes -- History; Industry; Industry & industrial studies